Knowledge, attitude, and practice of pesticide use by vegetable growers in Bangladesh: a health literacy perspective in relation to non-communicable diseases - Shahidullah, A. K. M.; Islam, Anisul; Rahman, Mokhlesur (Frontiers in Sustainable Food Systems, 2023)
Pesticides are widely used by vegetable growers in Bangladesh, however the health consequences of these chemicals in relation to non-communicable diseases (NCDs) is largely unknown. NCDs have emerged as a major health concern in recent decades and cause deaths, chronic illnesses, and psychosomatic suffering for people worldwide. In Bangladesh, a lack of health literacy among other reasons contributes to the occurrence and prevalence of NCDs. This study interprets and evaluates the status of key health literacy forming components, such as knowledge, attitude, and practices (KAP) of vegetable growers with respect to the use of pesticides. The study was carried out in six districts of Bangladesh. A multistage sampling procedure was used to obtain a survey sample of 334 farmers who grow vegetables and use pesticides. The results revealed that the level of knowledge of the farmers is poor. They are also not very aware of the relationship between pesticide use and potential vulnerability to NCDs. Such knowledge, along with attitude and practices developed through long-held beliefs and perceptions are not helpful for the safe and appropriate use and application of pesticides. To redress such KAP situations among vegetable growers, we posit that policy actors and stakeholders across public health and agricultural sectors, and developmental agencies must strive to improve health literacy in terms of KAP. Large-scale programmatic interventions in the knowledge, attitude, and practices of vegetable growers through training, education, or mass promotion could enhance their literacy and diminish the unabated use of pesticides.